The Influence of Loose Part Media on Speech Skills in Early Childhood Aged 5-6 Years in Islamic Kindergarten Harapan Ibu - Jannah, Miftahul; Puridawaty, Brigita (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to determine the extent of the influence of the use of Loose Part media on the speaking ability of early childhood aged 5-6 years in Harapan Ibu Islamic Kindergarten. This study is quantitative research paying attention to and revealing the extent of the influence of the use of Loose Part Play media on the ability to speak through storytelling methods of Early Childhood children aged 5-6 years in Group B of Harapan Ibu Islamic Kindergarten by comparing the learning outcomes of the experimental class with the control class. The experimental class was given action (X) while the control class was given action (Y) Students involved in this study were Group B Class B1 and B2, with a total of 30 students. Class B1 is an experimental class using a learning process with loose part media, while class B2 uses conventional learning. Techniques in collecting data using research instruments in the form of indicators that will be achieved as many as 14 items, which are carried out through action tests. The statistical program used for all statistical analysis in analyzing the data obtained during the study used SPSS 20.0, using normality, homogeneity, and hypothesis tests. Based on data analysis, the post-test results of the experimental class were greater than the control class, namely 74.40 for the experimental class and 57.60 for the control class. The resulting data is normally distributed and homogeneous. The Independent Sample T Test (mean) in the experimental class was 74.40 greater than the average value (mean) in the control class which was 57.60. So it can be concluded that there is a significant influence of Loose Part Media on Speech Ability in Early Childhood Aged 5-6 Years Group B in Harapan Ibu Islamic Kindergarten.